Enhancing Student Learning Motivation in Physics Through Interactive Physics Education Technology (PhET) Simulation - Manlapig, Ernesto (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: This research study aims to determine the effect of PhET simulation on the learning motivation of grade 12 STEM students in physics, specifically in projectile motion.Methodology: This study employed a quasi-experimental research design. A convenience sampling technique was utilized with a sample size of thirty-three (n=33) senior high school Grade 12 STEM students from a private institution in Malolos, Bulacan. The quantitative data of this research was obtained through the Students Motivation Toward Physics Learning Questionnaire (SMTPLQ) and a semi-structured interview with random students. The data was analyzed using average mean, p-value, and paired-samples t-test using SPSS 22 software.Main Findings: The learning motivation of the students in physics before the implementation of the PhET simulation was 3.82 (76.4%), which was medium-level motivation. After the implementation of the PhET simulation, the student's motivation in physics was 3.85 (77%), suggesting there was no statistically significant effect after using the PhET simulation. Despite no significant impact on motivation, students appreciated the engaging interaction with PhET simulations.Novelty/Originality of this study: This research introduces a novel approach by integrating PhET simulations to enhance student learning motivation in physics. By leveraging interactive and engaging virtual experiments, this study aims to foster a deeper understanding and interest in physics concepts among students. Using PhET simulations offers a dynamic learning environment that encourages active participation and exploration, revitalizing traditional teaching methods.